PROGRAM APLIKASI PENGELOLAAN KAS MENGGUNAKAN MICROSOFT VISUAL BASIC 2015 PADA MASJID AL JIHAD BANJARMASIN - Karima Zam Zam; Veri Julianto; Billy Sabella; Heldalina Heldalina (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2021)
Research purposes. This study aims to determine the proper cash management at Al Jihad Mosque, and to produce a computer-based Cash Management Application Program using Microsoft Visual Basic 2015 as the Front End, and Sql Server 2014 as a back end at the Al Jihad Mosque in Banjarmasin. Theoretical thinking framework. In this study the theoretical framework is analyzing the cash management that runs on the Al Jihad Mosque in Banjarmasin, by analyzing the information needed by management, related functions, accounting documents and records used, and flowcharts. The application program that was developed in the first step was carried out with relations between tables, designing interfaces, and designing outputs. Research result. The results of this study concluded that all cash records are semi-computerized. However, the author recommends using Microsoft Visual Basic 2015 as a Front End, and Sql Server 2014 as a back end so that it can help Al Jihad Mosque to record cash receipts and disbursements quickly and precisely.